EFISIENSI DANA HIBAH, KREATIVITAS, PENDAMPINGAN DAN IMPLEMENTASI TEKNOLOGI TEPAT GUNA PADA NILAI EKONOMI HASIL USAHA MITRA - Sunarso Sunarso; Taufik Taufik; Irwan Kurniawan (Jurnal Pengembangan Wiraswasta, 2019)
This paper analyzed the efficiency of grant fund, creativity, assistance and implementation of appropriate technology on the economic value of the partner’s business results based on the technological dissemination at two farmer groups that have been chosen as partners of the program. The objects of this research are two groups of farmers namely KUBE Sukamakmur and Saung Cipamingkis Farmers Groups in the village of Sukamulya, Bogor. Data collection methods used field observations and interviews with respondents consisting of partner farmers. It consists of 20 DMUs that divided into 5 food commodity clusters from 2 partner groups.The interview aims to obtain a general picture of the food crop farming of the farmers who are partners who are the object of research. Analysis of research data based on Data Envelopment Analysis (DEA). The research result showed that in the aspect of fund efficiency which has a technical efficient value reaches 100% only in 2 DMUs, namely DMU 19 and DMU 10, which are cluster S (cassava commodities). In the creativity efficiency, it can be seen that only in DMU 19 and DMU 20 (cluster S or cassava commodity) are efficient. The level of relative efficiency in the mentoring efficiency there was only 1 DMU which is efficient, namely DMU 19 in cluster S (cassava commodity). The level of efficiency in the aspect of appropriate technology (technical efficiency), only achieved by 1 DMU, namely DMU 19 in cluster S (Cassava). This also shows that as many as 19 DMU are marked inefficiencies from the acquisition of efficiency values